2009
DOI: 10.1021/ja810092k
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Dynamics of Guanosine Monophosphate in Water from Broad-Band Transient Absorption Spectroscopy and Quantum-Chemical Calculations

Abstract: Guanosine monophosphate (GMP) in aqueous solutions has been studied with femtosecond broad-band transient absorption spectroscopy and by quantum-mechanical calculations. The sample was excited at 267 or 287 nm and probed between 270 and 1000 nm with 100 fs resolution, for various pH values between 2 and 7. At pH 2, when the guanine ring is ground-state protonated (GMPH(+)), we observe isosbestic behavior indicating state-to-state relaxation. The relaxation is biexponential, tau(1) = 0.4 ps, tau(2) = 2.2 ps, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
301
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(357 citation statements)
references
References 65 publications
53
301
3
Order By: Relevance
“…There is still debate regarding the specific assignment of the multiexponential decay components. Some authors have assigned the relaxation pathways to nonadiabatic transitions among multiple electronic states [1,4,109], whereas others have assigned them to diabatic relaxation pathways occurring on a single potential energy surface [82,89,[110][111][112]. Another general observation is that conical intersections, i.e., points of degeneracy between two or more potential energy surfaces in the nuclear coordinate space of the molecule [113][114][115][116], play a key role in the ultrafast deactivation of the excited-state electronic energy in all the nucleic acid monomers [109,110,[116][117][118][119][120][121][122][123][124].…”
Section: Time-resolved Photophysical Properties Of the Nucleic Acid Mmentioning
confidence: 99%
“…There is still debate regarding the specific assignment of the multiexponential decay components. Some authors have assigned the relaxation pathways to nonadiabatic transitions among multiple electronic states [1,4,109], whereas others have assigned them to diabatic relaxation pathways occurring on a single potential energy surface [82,89,[110][111][112]. Another general observation is that conical intersections, i.e., points of degeneracy between two or more potential energy surfaces in the nuclear coordinate space of the molecule [113][114][115][116], play a key role in the ultrafast deactivation of the excited-state electronic energy in all the nucleic acid monomers [109,110,[116][117][118][119][120][121][122][123][124].…”
Section: Time-resolved Photophysical Properties Of the Nucleic Acid Mmentioning
confidence: 99%
“…65 In the solution phase, Gua itself is rarely studied as it has poor solubility, although dGMP -has been studied in a number of experiments with transient absorption 1,16,66 and fluorescence upconversion. 14, 16, 19, 67 14, 16, 19, 64 As for gas phase Gua excited at around 4.7 eV, solvated dGMP -is observed to relax through biexponential kinetics.…”
Section: Dgmp -mentioning
confidence: 99%
“…Furthermore, resonance Raman experiments have shown shown that uracil-like molecules keep a planar geometry during the first femtoseconds after the excitation of S π ,. 13 Triggered by the increasing amount of experimental findings, quantum chemistry calculations at various levels were dedicated to the study of the excited state behavior of the NABs and have provided a very rich source for understanding the mechanisms at the origin for their exceedingly short lifetimes 7,10,[14][15][16][17][18][19][20][21][22] The picture emerging from these experimental and theoretical studies is that the ultrafast decay of the first singlet excited state S * is due to highly efficient conical intersections (CI) between this state and the ground state (S 0 ). Very loosely speaking, for the pyrimidines, the internal conversion through the CI involves a pyramidalization of C 5 and/or a torsion of the C 5 C 6 bond accompanied by an out-of-plane motion of the 5-substituent (see Figure 1 for atom labelling).…”
Section: Ultrafast and Effective Non-radiative Decay Routes Exist Formentioning
confidence: 99%
“…We underline that such non-exponential decays are not necessarily due to the involvement of several electronically excited states. Two detailed studies of guanosine 5'-monophosphate (GMP) 7 and 2'-deoxyguanosine 5'-monophosphate (dGMP) 26 show clearly that the correspondence "one time constant -one electronic state"…”
Section: Ultrafast and Effective Non-radiative Decay Routes Exist Formentioning
confidence: 99%